Análisis de series temporales pluviométricas en la Cuenca del Duero - Herrero, Miguel A.; Álvarez, Rodrigo (Observatorio Medioambiental, 2007)
Time series of monthly rainfall values, given in mm/m2, for eight stations in the Spanish Duero river basin are analysed. They have been recorded during a long period of time, ranging from 83 to 140 years. Box-Jenkins techniques of identification, estimation and verification are employed to determine seasonal and non seasonal models. The seasonal model for the eight series has been identified as ARIMA (0,1,1) type. The results of the analysis show that the topography is a significant factor and, in some measure, explain higher mean annual values of rainfall in the north and western stations (Burgos 38.6, León 45.0 y Soria 45.4) than in the south and eastern locations; Salamanca 23.0 and Zamora 28.5. The seasonal analysis confirms the known patterns described as dry winters and summers with rainy springs and autumns